Ta có\(\frac{1}{x}+\frac{1}{y}=\frac{1}{3}\)(x;y > 0)
=> \(\frac{x+y}{xy}=\frac{1}{3}\)
=> 3(x + y) = xy
=> 3x + 3y = xy
=> xy - 3x - 3y = 0
=> x(y - 3) - 3y + 9 = 9
=> x(y - 3) - 3(y - 3) = 9
=> (x - 3)(y - 3) = 9
Vì x;y > 0
=> x - 3 > -3 ; y - 3 > -3 (1)
mà 9 = 1.9 = (-1).(-9) = 3.3 = (-3).(-3) (2)
Từ (1)(2)
=> x - 3 = 1 ; y - 3 = 9
=> x = 4 ; y = 12
hoặc x = 12 ; y = 4
Vậy các cặp (x ; y) thỏa mãn là (4;12);(12;4)
Ta có \(\frac{1}{x}+\frac{1}{y}=\frac{1}{3}\)
\(\Leftrightarrow\frac{y}{xy}+\frac{x}{xy}=\frac{1}{3}\)
\(\Leftrightarrow\frac{x+y}{xy}=\frac{1}{3}\)
\(\Leftrightarrow3\left(x+y\right)=xy\)
\(\Leftrightarrow3x+3y-xy=0\)
\(\Leftrightarrow\left(x-3\right)\left(y-3\right)=9\)
\(\Leftrightarrow\left(x-3\right)\left(y-3\right)=9=3.3=\left(-3\right).\left(-3\right)=1.9=9.1=\left(-1\right)\left(-9\right)=\left(-9\right)\left(-1\right)\)
\(th1\hept{\begin{cases}x-3=3\Leftrightarrow x=6\\y-3=3\Leftrightarrow y=6\end{cases}}\left(tm\right)\)
\(th2\hept{\begin{cases}x-3=-3\Leftrightarrow x=0\\y-3=-3\Leftrightarrow y=0\end{cases}}\left(ktm\right)\)
\(th3\hept{\begin{cases}x-3=1\Leftrightarrow x=4\\y-3=9\Leftrightarrow y=12\end{cases}}\left(tm\right)\)
\(th4\hept{\begin{cases}x-3=9\Leftrightarrow x=12\\y-3=1\Leftrightarrow y=4\end{cases}}\left(tm\right)\)
thử các cặp còn lại rồi kl